SOSIALISASI PENCEGAHAN GANGGUAN BABY BLUES DENGAN TERAPI SPIRITUAL EMOTIONAL FREEDOM TECHNIQUE (SEFT) - Muhammad Alyf Attaqy; Dwi Hurriyati (Jurnal Abdimas Bina Bangsa, 2023)
The puerperium is when the mother has days that are physically and mentally demanding compared to during pregnancy, which increases stress/depression. Because they are not enthusiastic about breastfeeding, mothers who experience excessive stress reduce their interest and interest in their babies and their ability to care for their children properly, so that the baby's health and growth and development are not optimal. The novelty of this community service can provide training on how to prevent baby blues. This assistance involved Posyandu cadres and pregnant women in Tebing Suluh Village, Lempuing District, Ogan Komering Ilir District, South Sumatra. The purpose of this activity is to increase people's understanding of the prevention of baby blues, self-identification and residents' understanding of baby blues. The event target is 20 people. The surgical method was carried out twice by providing counseling, ice breaking, and then group therapy. The assessment was carried out by asking the cadre's understanding of the prevention of baby blues. Regarding these results, through this activity, the people of Tebing Suluh Village received socialization about baby blues disorders. Stopping pregnancy counseling can prevent baby blues